The Carbon-Sulfur Link in the Remineralization of Organic Carbon in Surface Sediments - Bradbury, Harold J.; Turchyn, Alexandra V.; Bateson, Adam; Antler, Gilad; Fotherby, Angus; Druhan, Jennifer L.; Greaves, Mervyn; Sevilgen, Duygu S.; Hodell, David A. (Frontiers in Earth Science, 2021)
Here we present the carbon isotopic composition of dissolved inorganic carbon (DIC) and the sulfur isotopic composition of sulfate, along with changes in sulfate concentrations, of the pore fluid collected from a series of sediment cores located along a depth transect on the Iberian Margin. We use these data to explore the coupling of microbial sulfate reduction (MSR) to organic carbon oxidation in the uppermost (up to nine meters) sediment. We argue that the combined use of the carbon and sulfur isotopic composition, of DIC and sulfate respectively, in sedimentary pore fluids, viewed through a δ13CDIC vs. δ34SSO4 cross plot, reveals significant insight into the nature of carbon-sulfur coupling in marine sedimentary pore fluids on continental margins. Our data show systemic changes in the carbon and sulfur isotopic composition of DIC and sulfate (respectively) where, at all sites, the carbon isotopic composition of the DIC decreases before the sulfur isotopic composition of sulfate increases. We compare our results to global data and show that this behavior persists over a range of sediment types, locations and water depths. We use a reactive-transport model to show how changes in the amount of DIC in seawater, the carbon isotopic composition of organic matter, the amount of organic carbon oxidation by early diagenetic reactions, and the presence and source of methane influence the carbon and sulfur isotopic composition of sedimentary pore fluids and the shape of the δ13CDIC vs. δ34SSO4 cross plot. The δ13C of the DIC released during sulfate reduction and sulfate-driven anaerobic oxidation of methane is a major control on the minimum δ13CDIC value in the δ13CDIC vs. δ34SSO4 cross plot, with the δ13C of the organic carbon being important during both MSR and combined sulfate reduction, sulfate-driven AOM and methanogenesis.